2011
DOI: 10.1093/hmg/ddr121
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide meta-analysis for severe diabetic retinopathy

Abstract: Diabetic retinopathy is a leading cause of blindness. The purpose of this study is to identify novel genetic loci associated with the sight threatening complications of diabetic retinopathy. We performed a meta-analysis of genome-wide association data for severe diabetic retinopathy as defined by diabetic macular edema or proliferative diabetic retinopathy in unrelated cases ascertained from two large, type I diabetic cohorts: the Genetics of Kidney in Diabetes (GoKinD) and the Epidemiology of Diabetes Interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
160
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(174 citation statements)
references
References 33 publications
4
160
1
1
Order By: Relevance
“…Investigating the polymorphisms associated with diabetic retinopathy may help us better understand the developmental pathway of diabetic retinopathy and lead to new targeted therapy in treating diabetes and preventing diabetic retinopathy. [69][70][71] rs6427247 near SCYL1BP1 Unmodifiable Positive rs6427247 near SCYL1BP1 positively associated with increased risk of severe diabetic retinopathy [69][70][71] rs899036 near API5 Unmodifiable Positive rs899036 near API5 positively associated with increased risk of severe diabetic retinopathy [69][70][71] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigating the polymorphisms associated with diabetic retinopathy may help us better understand the developmental pathway of diabetic retinopathy and lead to new targeted therapy in treating diabetes and preventing diabetic retinopathy. [69][70][71] rs6427247 near SCYL1BP1 Unmodifiable Positive rs6427247 near SCYL1BP1 positively associated with increased risk of severe diabetic retinopathy [69][70][71] rs899036 near API5 Unmodifiable Positive rs899036 near API5 positively associated with increased risk of severe diabetic retinopathy [69][70][71] …”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8]10,19,21,22,24,28,30,34,[38][39][40][42][43][44][47][48][49][50][51][52][53] 69 This is consistent with other genome-wide association studies in Caucasian and Mexican-American patients. 70,71 As the relationship between genetic polymorphisms and diabetic retinopathy is still a new and emerging field, some studies have demonstrated new associations between single nucleotide polymorphisms, but these studies have not yet been replicable. Further studies are thus warranted.…”
mentioning
confidence: 99%
“…194 In addition, genome-wide association studies have identified several single-nucleotide polymorphisms associated with ESRD in some but not all studies. [195][196][197][198] Prevention of DKD remains challenging. Although microalbuminuria and macroalbuminuria are attractive therapeutic targets for CVD prevention, there are no specific interventions directed at the kidney that prevent DKD.…”
Section: Kidney Diseasementioning
confidence: 99%
“…However, GWAS have been successfully utilized to identify loci associated with extreme phenotypes in a number of complex diseases. [99][100][101][102] As a consequence of the small number of NODAT cases, these results did not reach the conventional threshold for genome-wide significance. As described, the stringent diagnostic criteria were used to generate phenotypic homogeneity with reduced case numbers as a consequence.…”
Section: Strengths and Limitationsmentioning
confidence: 86%